Investigation of the association between circulating inflammatory proteins and encephalitis risk in Europeans by two-sample Mendelian randomization analysis - Yanwei Liu; Xilong Wang; Qiang Zhao; Jun Wei; Shiqiang Yang (Frontiers in Neurology, 2025)
BackgroundCytokines are powerful immune response factors that operate at inflammation sites and are also found in the blood. Nevertheless, research on encephalitis and these circulating inflammatory proteins is quite limited.MethodsThis study investigated the potential causal effects of 91 circulating inflammatory proteins on three different types of encephalitis using a two-sample Mendelian randomisation analysis. The data source for encephalitis was the latest Finngen_R12 dataset, released in 2024. The study investigated causal effects mainly using Steiger, MR-Egger, weighted median and inverse variance weighting (IVW) methods. In addition, sensitivity analyses were performed, including heterogeneity assessment, horizontal pleiotropy and leave-one-out techniques.ResultsIn this study, 91 circulating inflammatory proteins were subjected to MR analysis of causality with each of the three types of encephalitis. The results suggest that the inflammatory factors with a potential causal relationship with viral encephalitis are artemin, C-C motif chemokine 28, C-X-C motif chemokine 1, interleukin-10 and neurotrophin-3. Inflammatory factors potentially causally associated with acute disseminated encephalomyelitis are monocyte chemoattractant protein 2, interleukin-10 receptor subunit beta and matrix metalloproteinase-1. Inflammatory factors potentially causally associated with autoimmune encephalitis are C-C motif chemokine 28 levels and Macrophage inflammatory protein 1a levels.ConclusionThis study identifies potential causal effects of certain circulating inflammatory factors on susceptibility to three types of encephalitis. Although the exact mechanisms by which inflammatory proteins contribute to the pathogenesis of different encephalitis subtypes remain unclear, our findings provide new perspectives on these potential causal relationships.